UNDERGRADUATE STUDENTS’ PERCEPTIONS TOWARD BLENDED LEARNING THROUGH INSTAGRAM IN ENGLISH FOR BUSINESS CLASS - Sari, Fatimah Mulya; Wahyudin, Achmad Yudi (International Journal of Language Education, 2019)
Addressing the needs of the millennial students brings the implemention of blended learning using social network site in the teaching and learning process. Instagram becomes one of the most popular social network sites in Indonesia. It has been a potential teaching platform to help English teachers to facilitate language learning, especially for learners at the tertiary level. This paper is intended to explore the students’ perceptions toward English language learning and the implementation of Instagram in their English for Business class. Students’ attitudes toward English course should be investigated to form a basis for this further study. The subjects were 116 undergraduate students who took general English for Business course at the Faculty of Engineering and Computer Science, University of Teknokrat Indonesia. They were classified into three groups. The data gained were from observation, questionnaire, and interview. The data, then, were analyzed quantitatively and qualitatively. The results indicated that most students showed high positive perceptions in using Instagram in their learning since social network Instagram influenced their motivation, engangement, and attitudes. In addition, internet connection and its speed, misunderstanding, and miscommunication toward the materials and task instructions were considered as the problems that hamper their learning. Instagram might help the students to learn English Language. Thus, it is suggested to improve the teaching of technology skills by preparing suitable digital literacy in academic content.